2001
DOI: 10.1055/s-2001-15880
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Prescriptions for Neuroleptic Drugs: Tranquilizers rather than Antipsychotics

Abstract: Evaluation is urgently needed for those uses of neuroleptic drugs that, from a pharmacoepidemiological perspective, must be seen as their primary indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 2 publications
2
23
1
3
Order By: Relevance
“…The availability of second-generation antipsychotic agents with improved anxiolytic properties over first-generation agents (24), while oftering less sedation (25), has likely contributed to their clinical role in the treatment of anxiety disorders (11). The availability of antipsychotics with fewer shortterm anticholinergic and extrapyramidal effects than firstgeneration antipsychotics (26) may have also contributed to the observed increases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The availability of second-generation antipsychotic agents with improved anxiolytic properties over first-generation agents (24), while oftering less sedation (25), has likely contributed to their clinical role in the treatment of anxiety disorders (11). The availability of antipsychotics with fewer shortterm anticholinergic and extrapyramidal effects than firstgeneration antipsychotics (26) may have also contributed to the observed increases.…”
Section: Discussionmentioning
confidence: 97%
“…Potential adverse effects of antipsychotics, including metabolic, endocrine, and cerebrovascular risks, have been well documented (7)(8)(9), Sedative properties associated with antipsychotic medications (10) may help to explain their broadened use in nonpsychotic patients. Some have suggested that from a pharmaco-epidemiological perspective, these drugs should be considered "antineurotic" or "hypnotic" medications rather than antipsychotics (11), In this context, patients presenting with anxiety disorders represent a large potential population for antipsychotic treatment. Clinical guidelines recommend serotonin reuptake inhibitors and serotonin-norepinephrine reuptake inhibitors as first-line pharmacologie treatments for anxiety disorders (12), although a significant number of patients do not respond to an adequate trial of these medications.…”
Section: Discussionmentioning
confidence: 99%
“…Polysomnographic sleep studies in such patients have consistently documented changes in a variety of sleep parameters, including reduced total sleep time (TST), sleep efficiency, increased sleep fragmentation, sleep latency, and, more variably, reduced slow wave sleep and rapid eye movement (REM) sleep (Caldwell and Domino 1967;Zarcone et al 1987;Bench et al 1992;Lauer et al 1997;Keshavan et al 1998). So far, few studies have investigated the influence of antipsychotics on polysomnographically recorded sleep, despite altered sleep in schizophrenia and the widespread off-label use of such drugs for the treatment of sleep disturbance (Linden and Thiels 2001). Conventional antipsychotics, such as chlorpromazine, pimozide and haloperidol, generally improve measures of sleep continuity in schizophrenia (Kaplan et al 1974;Gillin et al 1977;Keshavan et al 1996;Maixner et al 1998) but frequently demonstrate extrapyramidal side effects.…”
Section: Introductionmentioning
confidence: 98%
“…20,21 Somnolence is a side effect of quetiapine treatment, leading to prescription in an off-label fashion when this side effect is desired. 22 The somnolence effect of quetiapine is thought to arise from its 5-HT 2 and H 1 receptor blockade capabilities, similar to those of medications used as sedatives, including the antidepressants mirtazapine, trazodone, and trimipramine. Qualitative sleep studies using the Pittsburgh Sleep Quality Index (PSQI) have shown improvements in the sleep quality of depressed patients after initiation of quetiapine therapy.…”
mentioning
confidence: 99%